Systematic proteome and proteostasis profiling in human Trisomy 21 fibroblast cells. Issue 1 (December 2017) - Liu, Yansheng; Borel, Christelle; Li, Li; Müller, Torsten; Williams, Evan; Germain, Pierre-Luc; Buljan, Marija; Sajic, Tatjana; Boersema, Paul; Shao, Wenguang; Faini, Marco; Testa, Giuseppe; et al.
Abstract Down syndrome (DS) is mostly caused by a trisomy of the entire Chromosome 21 (Trisomy 21, T21). Here, we use SWATH mass spectrometry to quantify protein abundance and protein turnover in fibroblasts from a monozygotic twin pair discordant for T21, and to profile protein expression in 11 unrelated DS individuals and matched controls. The integration of the steady-state and turnover proteomic data indicates that protein-specific degradation of members of stoichiometric complexes is a major determinant of T21 gene dosage outcome, both within and between individuals. This effect is not apparent from genomic and transcriptomic data. The data also reveal that T21 results in extensive proteome remodeling, affecting proteins encoded by all chromosomes. Finally, we find broad, organelle-specific post-transcriptional effects such as significant downregulation of the mitochondrial proteome contributing to T21 hallmarks. Overall, we provide a valuable proteomic resource to understand the origin of DS phenotypic manifestations. Trisomy 21 (T21) is a major cause of Down syndrome but little is known about its impact on the cellular proteome. Here, the authors define the proteome of T21 fibroblasts and its turnover and also map proteomic differences in monozygotic T21-discordant twins, revealing extensive, organelle-specific changes caused by T21.